2015
DOI: 10.1007/s12311-015-0726-0
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar Contribution to Pattern Separation of Human Hippocampal Memory Circuits

Abstract: The cerebellum is a crucial structure for cognitive function as well as motor control. Benign brain tumors such as schwannomas, meningiomas, and epidermoids tend to occur in the cerebellopontine angle cisterns and may cause compression of the posterior lateral cerebellum near the superior posterior fissure, where the eloquent area for cognitive function was recently identified. The present study examined cognitive impairment in patients with benign cerebellar tumors before and after surgical intervention in or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 56 publications
1
19
0
Order By: Relevance
“…The fact that cerebellar Crus I/II (bilaterally) was involved in FTSD compared to ALS, could partially explain the cognitive impairment of these patients given the cerebellar role in memory, language processing and executive functions (Habas et al, 2009;Gellersen et al, 2017) as well in continuous cognitive processing tasks (Castellazzi et al, 2018). Interestingly, another study showed the involvement of postero-lateral cerebellum in psychomotor speed and working memory, particularly in differentiating two similar experiences (Shiroma et al, 2016). Furthermore, our study shows an involvement of the posterior cerebellum in FTSD compared to ALS, which could point to a greater disruption of the cerebro-cerebellar circuit in FTSD.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that cerebellar Crus I/II (bilaterally) was involved in FTSD compared to ALS, could partially explain the cognitive impairment of these patients given the cerebellar role in memory, language processing and executive functions (Habas et al, 2009;Gellersen et al, 2017) as well in continuous cognitive processing tasks (Castellazzi et al, 2018). Interestingly, another study showed the involvement of postero-lateral cerebellum in psychomotor speed and working memory, particularly in differentiating two similar experiences (Shiroma et al, 2016). Furthermore, our study shows an involvement of the posterior cerebellum in FTSD compared to ALS, which could point to a greater disruption of the cerebro-cerebellar circuit in FTSD.…”
Section: Discussionmentioning
confidence: 99%
“…The associations between the cerebellar cortex volume and the pattern separation ability suggest that the structure of the cerebellar cortex affects pattern separation. The cerebellum is closely associated with the pattern separation function (Shiroma et al, 2015).…”
Section: The Associations Between Pattern Separation Performance Anmentioning
confidence: 99%
“…and lateral cerebellum (Bakker et al, 2008;Shiroma et al, 2015). On the other hand, the function of reproducing neural patterns with complete information from incomplete information and recalling the memory after memory learning is termed the pattern completion, whose function is reported to be located in the hippocampal CA3 region for rodents (Rolls, 2013), and associated with the CA1 region in humans (Bakker et al, 2008).…”
mentioning
confidence: 99%
“…[ 2 8 13 ] In the first case, we performed surgery because the tumor was compressing the posterior lobe of cerebellum, causing a decline in cognitive function. [ 15 16 ] In the second case, surgery was performed because the patient exhibited signs of intracranial hypertension, such as headache and nausea. Hemangioblastomas have abundant blood flow comparable to arteriovenous malformations.…”
Section: Discussionmentioning
confidence: 99%